1995
DOI: 10.1074/jbc.270.42.24776
|View full text |Cite
|
Sign up to set email alerts
|

The α-Dendrotoxin Footprint on a Mammalian Potassium Channel

Abstract: ␣-Dendrotoxin, a 59-amino acid basic peptide from the venom of Dendroaspis angusticeps (green mamba snake), potently blocks some but not all voltage-dependent potassium channels. Here we have investigated the relative contribution of the individual ␣-subunits constituting functional Kv1.1 potassium channels to ␣-dendrotoxin binding. Three residues critical for ␣-dendrotoxin binding and located in the loop between domains S5 and S6 were mutated (A352P, E353S, and Y379H), and multimeric cDNAs were constructed en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 30 publications
2
38
1
Order By: Relevance
“…This 2 fold increase in APEKTx1 potency underlines that through-space electrostatic interaction is involved in APEKTx1 binding. These results are in corroboration with previously described similar observations for charybdotoxin binding to Shaker channels and for α-DTX binding to K V 1.1 channels [23][24][25]. In order to define the α-dendrotoxin footprint on mammalian potassium channels, 3 mutations (A352P, E353S and Y379H) were introduced in the dendrotoxin binding site, located in the H5 loop between the 6 transmembrane domains S5 and S6 of K V 1.1 subunits (fig.…”
Section: Electrophysiological Experimentssupporting
confidence: 75%
See 1 more Smart Citation
“…This 2 fold increase in APEKTx1 potency underlines that through-space electrostatic interaction is involved in APEKTx1 binding. These results are in corroboration with previously described similar observations for charybdotoxin binding to Shaker channels and for α-DTX binding to K V 1.1 channels [23][24][25]. In order to define the α-dendrotoxin footprint on mammalian potassium channels, 3 mutations (A352P, E353S and Y379H) were introduced in the dendrotoxin binding site, located in the H5 loop between the 6 transmembrane domains S5 and S6 of K V 1.1 subunits (fig.…”
Section: Electrophysiological Experimentssupporting
confidence: 75%
“…APEKTx1 however, is able to completely inhibit the current. Because APEKTx1 did not alter channel gating and binding was reversible we investigated whether APEKTx1 blockage followed the kinetic behavior of a bimolecular reaction [23]. Figure 4F shows the effects of increasing concentrations APEKTx1 on a K V 1.1 channel.…”
Section: Electrophysiological Experimentsmentioning
confidence: 99%
“…Thus toxin K will be useful in separating out the contributions from Kvl.1 subunits from other mammalian Shaker-family subunits in native cells, such as central neurones. Recent work [7] has shown that only one of the four c~ subunits in a tetrameric Kvl.1 potassium channel is necessary to confer sensitivity to ~-dendrotoxin (a close homologue of toxin K); here there is a linear relationship between the free energy of c~-dendrotoxin binding and the …”
Section: Discussionmentioning
confidence: 99%
“…Having checked that its CD spectrum was identical to that of BgK, we examined its blocking capacity on rKv1.1, rKv1.2, and rKv1. 37-41), they are all likely to bind to the P-region of Kv1 channels (32,(42)(43)(44)(45)(46). Recent progress has characterized the sites by which these peptides bind to the vestibule of Kv1 channels (14, 16 -17, 27, 32-33, 36, 47-50), and comparison of these sites revealed that all of these blockers possess at least a common diad composed of two functionally important residues: a lysine and an hydrophobic residue (32,36).…”
Section: Contribution Of the Diad Lys-25/tyr-26 In The Bgkmentioning
confidence: 99%